Design of Website-Based Learning Media to Enhance Critical Thinking Skills in Static Fluid Concepts - M Hermana; Agus Danawan; Arif Hidayat (Jurnal Penelitian Pembelajaran Fisika, 2025)
Critical thinking skills are one of the 21st-century skills that students must have, and the rapid development of technology provides a demand to develop a learning medium that facilitates this. Therefore, the purpose of this research is to create a website-based learning media design oriented to critical thinking skills on static fluid material. The research utilises the Successive Approximation Model (SAM) for its development. The research model consists of a preparation phase, an iterative design phase, and a final phase. The preparation phase is the initial stage to efficiently collect background information on the problem. The iterative design phase consists of design cycle activities, prototyping, and reviewing. The iterative design phase includes the process of developing, implementing, and evaluating learning media continuously. The research participants consisted of lecturers, prospective teachers, teachers, and students. The feasibility of the website was analysed in terms of material and media, which was conducted twice by six validators. In the first stage, the feasibility of the website in terms of material and media was declared "Feasible" with a V-aiken score of 0.600. After making improvements, the website was revalidated with a V-aiken score of 0.926 with the category "Feasible". Students' responses to the developed website were positive. The website's readability is excellent. This website-based learning media has contributed to meeting the demands of students' critical thinking skills.